Book Review: The Crisis of the European Union. A Response - Alina Bârgăoanu; Loredana Radu (Romanian Journal of European Affairs)
In his book “The Crisis of the European Union”, Jurgen Habermas explored the options available for the European Union in dealing with the global crisis. The author structured his approach on two essays. The first one, entitled “The Crisis of the European Union in Light of a Constitutionalization of International Law - An Essay on the Constitution for Europe”, emphasizes the fact that while the European decisionmakers have focused on solving the currency, banking and debt crises, they omitted the political dimension of the crisis. Moreover, the author considers that in the light of a constitutional treaty for Europe, the transnationalization of the European democracy will be possible if both the public opinion and the politicians can overcome three categories of preconceptions: the dependence of the popular sovereignty to the state sovereignty, the mutually exclusive status of the European citizenship and of the national one, the indivisible nature of the sovereignty. The second essay, entitled “The Concept of Human Dignity and the Realistic Utopia of Human Rights” underlines the imperative nature of the human rights and human dignity interconnected concepts. He states that two conditions must be met in order for the concepts to be valid. Habermas considers that there must be a political community that enacts them and that the two concepts are universally accepted. The Appendix includes three recent political interventions through which Habermas reiterates the uncomfortable and controversial topic of European unification. He concludes that the European Project cannot be allowed to fail because of the raise of German nationalism and the lack of visionary European leadership.